Catalysts or antidotes to downward social mobility? Critique of the "Big Three" in Zimbabwe - Madzokere, Nyasha (HTS teologiese studies, 2024)
The fact that Pentecostal Christianity is the fastest growing form of Christianity in Africa can no longer be a subject of debate. Christianity, one of the major religions in the world, has been growing at unprecedented rates in sub-Saharan Africa. What is being observed on the religious atmosphere is the Pentecostalisation of African Christianity in Africa in general and Zimbabwe in particular. From 2009 onwards, Zimbabwe has experienced a mushrooming spree of contemporary Pentecostalism. Though conglomerate in nature, three ecclesiastical figures overshadow the rest, namely Emmanuel Makandiwa’s United Family International Church, Uebert Angel of Good News Church and Walter Magaya of Prophetic, Healing and Deliverance Ministries. The three Pentecostal figures became highly popular through the propagation of the Gospel of Prosperity with vigour and vitality. Their presence in the Zimbabwean religious arena has attracted mixed perceptions. Some people view them as rippers of peoples’ hard-earned monies, while others regard them as true prophets – the messengers of God. The million-dollar question remains: Are they catalysts or antidotes to downward social mobility? This article grapples to assess whether the ‘Big Three’ contemporary Pentecostal prophets serve as propellers or dispellers of downward social mobility. The Big Three are antidotes based on three arguments: (1) Propagation of the Gospel of Prosperity, (2) miracle performances and (3) societal empowerment champions. On the other hand, the prophets are catalysts based on three arguments: white-collar prophecy, negation of social justice and preferential option for the Powerful. Through the application of the justitia pro-povo oprimido liberation hermeneutics, the study argues that the ‘Big Three’ ecclesiastical clergymen serve more as catalysts to downward social mobility than antidotes to downward social mobility. The justitia pro-povo oprimido liberation hermeneutics is a new methodological approach invented by the author based on liberation theology that sees Christianity as seeking the justice of the oppressed.Contribution: The article critically reflects on rise of contemporary Pentecostalism in Zimbabwe focussing on the three outstanding prophets – Emmanuel Makandiwa, Uebert Angel and Walter Magaya. While the three clergymen contributed immensely, both positively and negatively to the rise and development of African Pentecostalisation of Zimbabwe, the justitia pro-povo oprimido liberation hermeneutics reveals the contemporary Pentecostal figures as propellers of downward social mobility.